Christmas in Camelot: Magic Tree House "Merlin Missions" # 1 - Osborne, Mary Pope, 1949-; Murdocca, Sal (New York : Random House, 2009)
On Christmas Eve, Jack and Annie's tree house transports them to King Arthur's castle at Camelot, where they undertake a quest to the castle of the Otherworld.
Reprint. Originally published: c2001.
"A Merlin Mission."
"A Stepping Stone book."
"With a Christmas ornament!"--Cover.
Keywords: Christmas -- Fiction; Time travel -- Fiction; Magic -- Fiction; Christmas -- Fiction; Tree houses -- Fiction; Siblings -- Fiction; Camelot (Legendary place) -- Fiction; Tree houses -- Fiction; Siblings -- Fiction